Effects of anthropometric parameters and stride frequency on estimation of energy cost of walking - Bereket, S. (The Journal of Sports Medicine and Physical Fitness, 2005)
Aim: This study was conducted to develop a generalized, multifactorial walking equation for estimating VO2 during treadmill walking at self-selected treadmill belt speeds. Also, the study sought to find the stride frequency (SF) and stride length (SL) combination which yielded the highest VO2. Methods: The participants for this study included 100 university students (50 male and 50 female) between the ages of 18 and 57. After standing height, sitting height, hip breadth, calf length, thigh length, and gross body mass were measured, the preferred speed (Pv), self-selected as being challenging but comfortable, was determined for each subject at 0% grade. Subsequently, a 2nd walk test was conducted at Pv utilizing 5 different SF which were paced by means of a metronome. In each of these 5 SF-SL combinations, heart rate and metabolic data were recorded. Results: Stepwise regression analysis showed that calf length and treadmill belt speed were two independent variables that account for significant increase in variance in which VO2 at preferred stride Frequency (PSF)-15 strides was used as dependent variable. Split plot ANOVA results indicated that the participants' VO2, heart rate, and breathing frequency responses were significantly (p<0.05) lower at PSF when compared to the other 4 SF conditions. Conclusion: Research indicated that other than velocity of walking, anthropometric characteristic such as calf length has a significant effect on estimation of energy cost of walking. Furthermore, cardiovascular loading can be affected by manipulating SL and SF as alternate forms of training in regimens of walking.